2020
DOI: 10.21831/jipi.v6i1.32637
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Indonesia and Singapore based on PISA 2015: Five-factor students’ perception in science education

Abstract: As a neighbouring country whose location is very close, there is a unique fact where the results of the PISA study show very different results between Indonesia and Singapore. Students' perceptions of learning have an important role to detect the quality of learning. Thus, this study aims to determine the factors of student perception of natural science learning and the differences between the two countries based on these factors. The sample in this study were 5870 Indonesian students and 5272 Singapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Thus, something logical will be found in the various impact of technology on language learning quality. It makes sense that the findings from each country's data show different impacts since each country has specific educational criteria [60]. However, in general, it is found that technology is able to support language learning output quality.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, something logical will be found in the various impact of technology on language learning quality. It makes sense that the findings from each country's data show different impacts since each country has specific educational criteria [60]. However, in general, it is found that technology is able to support language learning output quality.…”
Section: Discussionmentioning
confidence: 99%
“…Pembelajaran IPA menekankan pada pemberian pengalaman secara langsung sehingga memberikan keaktifan siswa di Sekolah Dasar. IPA berhubungan dengan cara mencari tahu tentang alam secara sistematis, sehingga bukan hanya penguasaan kumpulan pengetahuan yang berupa fakta-fakta, konsep-konsep, atau prinsip-prinsip saja tetapi juga merupakan suatu proses penemuan (Arlinwibowo et al, 2020;Awe & Benge, 2017). Pembelajaran IPA di Sekolah Dasar mencakup materi pengetahuan alam yang sering dijumpai peserta didik dalam kehidupannya, maka dari itu pembelajaran IPA yang bermakna adalah pembelajaran yang relevan dengan kehidupan sehari-hari (Maryanti et al, 2021).…”
Section: Pendahuluanunclassified
“…Additionally, the science domain presents challenges, as some students perceive it as overly theoretical and difficult to comprehend . Lastly, engineering and technology domains are based on complex concepts, requiring students to master high-level thinking skills for effective learning (Arlinwibowo et al, 2020b;Arlinwibowo et al, 2021a). Despite these challenges, many students are capable of mastering STEM subjects.…”
Section: Introductionmentioning
confidence: 99%